A Business of His Own. - Gao Yulei (Beijing Review, 2007)
The Chinese entrepreneur Wu Xisang, a former computer programmer, has developed into a competent CEO. Wu, now 34, was one of the earliest Chinese beneficiaries of the Internet boom; he started his first company after graduating from college in 1995 and is now on his fifth start-up. The fact that he sold his first four companies earned him the nickname Taoxian Chengxuyan, or “the programmer who keeps cashing out.” After two investment rounds totaling $10 million for his current company, Huoshi Software, he has had to resist the temptation to cash out for the fifth time in order to put his nickname behind him.